2007
DOI: 10.1074/jbc.m703848200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Sterol Binding by NPC2, a Lysosomal Protein Deficient in Niemann-Pick Type C2 Disease

Abstract: NPC2 is a small lysosomal glycoprotein that binds cholesterol with submicromolar affinity. Deficiency in NPC2 is the cause of Niemann-Pick type C2 disease, a fatal neurovisceral disorder characterized by accumulation of cholesterol in lysosomes. Here we report the crystal structure of bovine NPC2 bound to cholesterol-3-O-sulfate, an analog that binds with greater apparent affinity than cholesterol. Structures of both apo-bound and sterolbound NPC2 were observed within the same crystal lattice, with an asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
254
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(269 citation statements)
references
References 36 publications
12
254
0
Order By: Relevance
“…4A Inset and data not shown). The human P120S mutation replaces a residue that lies at the edge of the hydrophobic cholesterol-binding pocket as indicated by the crystal structure of the bovine NPC2 (11). Indeed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A Inset and data not shown). The human P120S mutation replaces a residue that lies at the edge of the hydrophobic cholesterol-binding pocket as indicated by the crystal structure of the bovine NPC2 (11). Indeed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NPC2 has been shown to bind cholesterol and derivatives such as cholesterol sulfate (8)(9)(10). X-ray crystallography reveals that cholesterol sulfate binds in such a manner that the iso-octyl side chain of the sterol is deeply buried in a hydrophobic pocket and the sulfate on the 3 position of the A ring is exposed to solvent (11). Introduction of a hydrophilic moiety, such as a hydroxyl group, on the cholesterol side chain prevents binding (10).…”
mentioning
confidence: 99%
“…Careful molecular dissection of NPC1 revealed that the soluble NTD of NPC1 [NPC1(NTD)] contained all of the sterol binding capacity of NPC1 and bound oxysterol stronger than cholesterol (9). This finding was in contrast to the soluble NPC2 protein that clearly showed a strong preference for cholesterol and did not bind oxysterols (8)(9)(10). Mutation of either NPC1 or NPC2 yields an identical Niemann-Pick disease etiology (1,5,6,12), suggesting that they work together in an unknown fashion to export cholesterol.…”
mentioning
confidence: 39%
“…Whether NPC1 functions as a transporter remains controversial. In contrast, NPC2 is a soluble, glycosylated protein that is present in the lumen of the LE (5,8) (Fig. 1).…”
mentioning
confidence: 99%
“…Mutant NPC1 cells show massive accumulation of cholesterol and glycosphingolipids in late endosomes and lysosomes. NPC2 is a cholesterol binding protein that binds cholesterol via its iso-octyl moiety (9) (Fig. 1).…”
mentioning
confidence: 99%